IMPROVING THE PROCEDURE FOR CONDUCTING AN AUDIT OF FINANCIAL PERFORMANCE REPORTS IN THE FIELD OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE CONTEXT OF ECONOMIC MODERNIZATION - Bekchanov Fakhriddin Atabekovich (Research Parks Publishers, 2023)
In this article, in the context of the modernization of the economy, suggestions are made for improving the procedure for conducting an audit of the financial results report in the field of information and communication technologies. Also, the problematic aspects of the audit of the financial results report were highlighted, and suggestions were made on them.